Determining the 2D spatial distribution of plasma parameters in a cylindrical cross section of a radio-frequency ion thruster by optical emission spectroscopy - Becker, Felix; Sarnoch, Pascal; Holste, Kristof; Leiter, Hans; Klar, Peter J.; Justus Liebig University Giessen (My University, 2025)
Gridded ion engines, such as the radio-frequency ion thruster, are highly efficient designs for generating thrust on satellites or spacecrafts for both commercial and scientific missions, due to the very high exhaust velocities achieved. A thorough understanding of the low-temperature and low-pressure plasma parameters is essential in order to characterize, design, and optimize such a thruster. Corresponding plasma parameters can be obtained non-invasively from empirical correlations between the results of Langmuir double probe measurements and optical emission spectroscopy. The plasma parameters can be extracted solely from the recorded optical emission spectra once such an empirical correlation is established for a specific experimental setup and various operation conditions. Light from an object plane at a specified depth within the plasma is focussed onto the projection plane, using a telescopic arrangement of lenses and an aperture. Despite being out of focus, the grid structure is still identifiable though slightly blurred. By carefully scanning across this image, taking spectra at every light spot, we can record a series of optical emission spectra where each spectrum corresponds to a plasma volume located in the object plane behind a grid hole. The object plane is a 2D cross section within the bulk of the plasma at a distance of 5 cm behind the grid. Our approach therefore allows us to monitor the spatial profiles of plasma parameters in this cross section of the RIT 10 for different operating points of the thruster. Such spatial profiles are essential for characterizing thruster performance and improving global modeling of such thrusters. We believe that this method is also applicable for RITs of other sizes in the context of space qualification.
Keywords: ddc:530